Formación inicial docente: experiencia de práctica comunitaria en contexto intercultural mapuche: Initial Teacher Training: Community Practice Experience in an Intercultural Mapuche Context - Bórquez Mella, Jessica Andrea; Sáez González, Joseline Anaís; Hernández Burgos, Deysi Camila (Universidad del Zulia, 2022)
This article analyzes the experience of community practice of future teachers of Natural Sciences and Biology at the Catholic University of Temuco, Chile. The service-learning strategy was implemented in a Mapuche intercultural context, in the region of La Araucanía. The research problem is related to the implementation of community practices in an intercultural context that considers social and cultural diversity, facilitating and improving the quality of life of the community from the problems that are revealed in it. The methodology was qualitative, the participatory action research design. Participant observation, trawün (Mapuche conversation) and documentary analysis were used. Content analysis was performed by coding and classifying the data. The results show the situated learning of the future teachers in the local community context, allowing them to build cultural knowledge together with the community partner. Likewise, they showed the appreciation of cultural diversity, which will allow them to perform in their professional future in intercultural contexts considering the transformation of their own knowledge and performance in the community.